Implementasi Peran Bahasa Indonesia Dalam Menghadapi Era Globalisasi Ditinjau Dari UU Nomor 24 Tahun 2009 - Satrio Wicaksono Adi (Jurnal Hukum dan Sosial Politik, 2024)
Bahasa plays a very important role for people and society, for example by creating a tool to maintain the exchange of ideas between, among, or within groups of people within a particular group. Groups are also considered personal identities. Communication is an activity that unites, connects and builds relationships between many people. This scientific work aims to formulate the problem of the role of Indonesian in facing the era of globalization. This research uses a literature review method, which means this method examines the results of analysis of various conceptual information as well as qualitative and quantitative data from various previously published scientific articles. Almost all agreements in Indonesia are dominated by long sentences, up to eighty to one hundred words in one sentence. This is ironic, because Indonesian shouldn't be like that, thus showing clichéd mistakes that keep repeating themselves and lead to uncertainty. In short, understanding Indonesian is no longer the responsibility of a linguist or writer, but also of legal practitioners as the spearhead of law enforcement in Indonesia.